Dietary Sugars Analysis: Quantification of Fructooligossacharides during Fermentation by HPLC-RI Method - Correia, Daniela M.; Dias, Luís G.; Veloso, Ana C. A.; Dias, Teresa; Rocha, Isabel; Rodrigues, Lígia R.; Peres, António M. (Frontiers in Nutrition, 2014)
In this work a simple chromatographic method is proposed and in-house validated for the quantification of total and individual fructooligossacharides (e.g., 1-kestose, nystose, and 1F-fructofuranosylnystose). It was shown that a high performance liquid chromatography with refractive index detector could be used to monitor the dynamic of fructooligossacharides production via sucrose fermentation using Aspergillus aculeatus This analytical technique may be easily implemented at laboratorial or industrial scale for fructooligossacharides mass-production monitoring allowing also controlling the main substrate (sucrose) and the secondary by-products (glucose and fructose). The proposed chromatographic method had a satisfactory intra- and inter-day variability (in general, with a relative standard deviation lower than 5%), high sensitivity for each sugar (usually, with a relative error lower than 5%), and low detection (lower than 0.06 ± 0.04 g/L) and quantification (lower than 0.2 ± 0.1 g/L) limits. The correct quantification of fructooligossacharides in fermentative media may allow a more precise nutritional formulation of new functional foods, since it is reported that different fructooligossacharides exhibit different biological activities and effects.